Gorenstein Quivers (São Paulo Journal of Mathematical Sciences, 2010)
We introduce a notion of Gorenstein quiver associated witha Gorenstein matrix. We study properties of such quivers. In partic-ular, we show that any such quiver is strongly connected and simplylaced. We use Perron-Frobenius theory of non-negative matrices forcharacterization of isomorphic Gorenstein quivers.